Lambert–Eaton myasthenic syndrome: Clinical review. Issue 3 (August 2016) - Motomura, Masakatsu; Nakata, Ruka; Shiraishi, Hirokazu
Abstract: Lambert–Eaton myasthenic syndrome (LEMS) is an autoimmune disease of the neuromuscular junction and approximately 60% of LEMS patients have a tumor, mostly small cell lung cancer, as a paraneoplastic neurological syndrome. LEMS patients develop a unique set of clinical characteristics, which include proximal muscle weakness, depressed tendon reflexes with post‐tetanic potentiation and autonomic symptoms. Interestingly, slightly <10% of LEMS patients have cerebellar ataxia (LEMS with paraneoplastic cerebellar degeneration). Considering its pathomechanism, LEMS is a presynaptic disorder of neuromuscular transmission in which quantal release of acetylcholine is impaired by autoantibodies for P/Q‐type voltage‐gated calcium channels at active zones, although an animal model by immunizing purified P/Q‐type voltage‐gated calcium channels has not yet been successful. Abstract : In the autopsy cerebellum of PCD‐LEMS patients, the number of P/Q‐type VGCCs of molecular layer is reduced.